Analisis Tingkat Kepercayaan Masyarakat Terhadap Transparansi dan Akuntabilitas Pengelolaan Keuangan Desa - Raudatuzzahra, Raudatuzzahra; Fadli, Fadli (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
This study aims to examine the effect of transparency and accountability in village financial management on the level of community trust in North Bengkulu Regency. This study uses purposive sampling. The data used were primary data collected through questionnaires distributed to 217 respondents with sample criteria for the Village Consultative Body (BPD). The data processing technique was carried out using the Partial Least Square (PLS) method assisted by SmartPLS software. The findings of this study are the path coefficient of transparency to public trust of 0.277 with a T-statistic of 2.389 and p value = 0.008, indicating that every one unit increase in transparency will increase public trust by 0.277 units, and this effect is significant at α = 5% (because p < 0.05). Meanwhile, accountability has a path coefficient of 0.588, a T-statistic of 5.002, and p < 0.001, which means that a one-unit increase in accountability increases the level of public trust by 0.588 units, with a much stronger level of significance. From the results of this test, transparency and accountability have a positive effect on the level of public trust.